Razão & dominação: Adorno e o dilema do materialismo histórico-dialético - Piva, Ricardo Ríspoli (2012)
All of the effort required for the present dissertation has been concentrated in a demonstration of the influence that the German Philosopher, Theodor Adorno, has had in the development of Dialectical, Historical Materialism. Adorno and other academics of the Frankfurt school elaborated a reexamination of Marxist methodology, in the first decades of the twentieth century, in light of the social phenomena of the time: fascism, and Stalinism; advanced stages of the crises of global Capitalism as symbolized by the blind flight of the Phoenix, accompanied by a relapse of the nation state and the unfortunate experiences with Socialism. The global managed world society, notably omnipresent following World War II, challenged Adorno in his excellent epistemological analysis to recognize that various manifestations of ideological thought, of international scope, have accumulated with the domination of nature as well as the domination of man, by man and the ensuing social relations that have engendered the present mode of production, consequences of the growing trends that are stifling even those with the most critical consciences. With the guidance of illustrious predecessors such as Lukacs, traditional Marxism has correctly focused research regarding crises on the philosophy of decadence which works to maintain the current status quo in order to perpetuate the social relations so that the bourgeoisie can retain itself as the subject of class history. By refuting the concept of class struggle as, for example, the possibility that the proletariat will substitute the decadent bourgeoisie, promoting social transformation, Adorno questions this orthodox interpretation of Marx: if theory and praxis are the same thing, only with the additional development of theory will the social practice be renewed. This is, obviously, independent of blind determinism manifested by some lines of thought and of a return to mythological metaphysics.